Anti-diabetic Plant Bioactive Compounds: Modern Drug Development from Traditional Herbal Medicine - Baile, Sunil B.; Hadia, Rajesh; Kardani, Sunil Kumar L.; Patel , Shivkant; Patel, Kinjal; Dash , Dillip Kumar (Multidisciplinary Approaches in Pharmaceutical Sciences, 2023)
It has been demonstrated that natural goods, including creatures (plants, animals, or microbes), provide advantages for both human and animal health. The World Health Organization estimates that 80% of the population in underdeveloped nations still relies on traditional or folk medicines, which are often made from plants, for illness prevention or treatment. Traditional medicine derived from plant extracts has shown to be more accessible, therapeutically successful, and to have comparatively less side effects than contemporary medications. According to published research, the pharmaceutical industry has given phytochemical components of therapeutic plants far more attention. Secondary metabolites produced by plants, such as steroids, alkaloids, phenolic compounds, lignans, carbohydrates, and glycosides, among others, have a variety of biological properties that are advantageous to people, including anti-inflammatory, anti-cancer, anti-microbial, anti-allergic, and antioxidant properties. As a result of metabolic abnormalities in hyperglycemic pancreatic cells, diabetes mellitus is a chronic illness. Type 1 diabetes mellitus and Type 2 diabetes mellitus both result in hyperglycemia due to insufficient pancreatic insulin production or insufficient insulin production as a result of insulin resistance. Thus, conventional medications play a significant role as alternative medications and have been in use for a long time. In addition, during the past several years, certain novel bioactive medicines derived from plants demonstrated more efficacy in the treatment of diabetes than oral hypoglycemic medications. The treatment of diabetes mellitus is a promising area for traditional medicine, which has a strong track record in clinical practice. According to the World Health Organization, preventing diabetes and its consequences is not just a significant issue for the future but also crucial if universal health is to be achieved. The active ingredients and pharmacological effects of a few well-known plants that have been utilized extensively in the treatment of diabetes are therefore briefly reviewed in this work. For the purpose of identifying each species of plant, morphological data from the V-herb database was also incorporated.